2018
DOI: 10.1021/acs.jpcc.7b12662
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Elevated-Temperature Photocatalytic Reduction of CO2 by H2O

Abstract: Photocatalytic reduction of CO 2 for the production of synthesis gas, hydrocarbons, alcohols, or aldehydes from only CO 2 , H 2 O, and solar radiation may be a promising route to recycle CO 2 waste at the source of its production, reduce atmospheric CO 2 through direct removal from Earth's atmosphere, and/or produce CH 4 rocket fuel on Mars. In this study, we present the first studies of high-temperature (350 °C) photocatalytic reduction of CO 2 in the gas phase over a suite of semiconductors with a range of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 75 publications
1
38
0
Order By: Relevance
“…atures. [43] Furthermore,p revious reports have also indicated that the reaction rates for semiconductor photocatalysts depend on the square root of the light intensity. [15] Therefore, in practical applications,i fwe want to increase the yield of products,t he efficiencies for general photocatalysts can be significantly reduced by increasing the light intensity,w hich might be ap otential factor that can hinder use of semiconductor photocatalysts because high-intensity light, especially IR light, will inevitably increase the temperature of the gas-solid reaction system.…”
Section: Research Articlesmentioning
confidence: 99%
“…atures. [43] Furthermore,p revious reports have also indicated that the reaction rates for semiconductor photocatalysts depend on the square root of the light intensity. [15] Therefore, in practical applications,i fwe want to increase the yield of products,t he efficiencies for general photocatalysts can be significantly reduced by increasing the light intensity,w hich might be ap otential factor that can hinder use of semiconductor photocatalysts because high-intensity light, especially IR light, will inevitably increase the temperature of the gas-solid reaction system.…”
Section: Research Articlesmentioning
confidence: 99%
“…In the past few years, a shift has been occurring where researchers have started to ask fundamental questions about the CO 2 photoreduction process. These questions include the following: What are the best analytical methods to track CO 2 photoreduction and what products, besides CH 4 and CO, are being formed from CO 2 photoreduction? What is the best mechanism for describing CO 2 photoreduction? What is the driving energy behind the CO 2 photoreduction mechanism? , What are the critical process parameters for CO 2 photoreduction? , What is the best experimental protocol for comparing photocatalysts for CO 2 photoreduction? …”
Section: Introductionmentioning
confidence: 99%
“…Photocatalysis on semiconductor photocatalysts has been well studied and provides an attractive approach for room temperature reactions, [41, 42] but a negative dependence of photocatalytic rates on operating temperature is commonly observed in semiconductor‐based photocatalysis because of the relatively low Debye temperatures of the semiconductors involved and significant recombination of photogenerated electron‐hole pairs even at moderately elevated temperatures [43] . Furthermore, previous reports have also indicated that the reaction rates for semiconductor photocatalysts depend on the square root of the light intensity [15] .…”
Section: Resultsmentioning
confidence: 99%
“…Photocatalysis on semiconductor photocatalysts has been well studied and provides an attractive approach for room temperature reactions, [41,42] but an egative dependence of photocatalytic rates on operating temperature is commonly observed in semiconductor-based photocatalysis because of the relatively low Debye temperatures of the semiconductors involved and significant recombination of photogenerated electron-hole pairs even at moderately elevated temper-Angewandte Chemie Forschungsartikel atures. [43] Furthermore,p revious reports have also indicated that the reaction rates for semiconductor photocatalysts depend on the square root of the light intensity. [15] Therefore, in practical applications,i fwe want to increase the yield of products,t he efficiencies for general photocatalysts can be significantly reduced by increasing the light intensity,w hich might be ap otential factor that can hinder use of semiconductor photocatalysts because high-intensity light, especially IR light, will inevitably increase the temperature of the gas-solid reaction system.…”
Section: Angewandte Chemiementioning
confidence: 99%